Early Reading Assessment for Children with Special Needs: A Basis for Program Recommendations in Inclusive Primary Schools - Nurfadilah, Agni; Nurkholifah, Dira Rosalia; ‘Aisy, Naurah Rahadatul; Rochyadi, Endang; Herlina, Herlina (research, training and philanthropy institution Natural Aceh, 2025)
This case study explores the learning profile of JN, a student exhibiting specific learning difficulties, particularly dyslexia. Through a comprehensive assessment process, it was found that JN faces persistent challenges in reading, especially in decoding syllables, words, and sentences, due to deficits in auditory perception, phonological awareness, and phoneme discrimination. Despite these difficulties, JN shows notable strengths in letter recognition, visual perception, and visual memory. These contrasting cognitive profiles suggest the need for targeted instructional interventions that utilize visual-based and multisensory learning strategies. The findings underscore the importance of early identification and individualized support within an inclusive education framework. Such an approach ensures that students with learning barriers receive equitable and effective educational opportunities that align with their unique strengths and needs.